2022
DOI: 10.1097/md.0000000000030607
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of adenosarcoma and the inverse probability of treatment weighting (IPTW) adjusted survival analysis of lymph node dissection in uterine adenosarcoma

Abstract: The objective for the study was to analysis the epidemiology of adenosarcoma, and independent prognostic factors and impact of lymph node dissection (LND) of uterine adenosarcoma. Cases of patients with primary adenosarcoma were obtained from the Surveillance, Epidemiology, and End Results (SEER) database from 2000 to 2016. Overall survival was analyzed by the Kaplan-Meier method and log-rank test. The differences in baseline covariates between the 2 groups were adjusted by inverse probability of treatment wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Surgical treatment (hysterectomy and bilateral salpingo-oophorectomy) represents the standard treatment for UA and it should be performed by an expert gynecologist oncologist in referral centres. Due to the low risk of regional lymph nodes metastasis, lymphadenectomy is not recommended [11] Currently there is no standardized specific radiation therapy, hormonal therapy or adjuvant chemotherapy for the treatment of UA. Adjuvant radiotherapy can be offered to low risk patient without sarcomatous overgrowth and less of 50% myometrial invasion [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical treatment (hysterectomy and bilateral salpingo-oophorectomy) represents the standard treatment for UA and it should be performed by an expert gynecologist oncologist in referral centres. Due to the low risk of regional lymph nodes metastasis, lymphadenectomy is not recommended [11] Currently there is no standardized specific radiation therapy, hormonal therapy or adjuvant chemotherapy for the treatment of UA. Adjuvant radiotherapy can be offered to low risk patient without sarcomatous overgrowth and less of 50% myometrial invasion [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low risk of regional lymph nodes metastasis, lymphadenectomy is not recommended [11] Currently there is no standardized specific radiation therapy, hormonal therapy or adjuvant chemotherapy for the treatment of UA. Adjuvant radiotherapy can be offered to low risk patient without sarcomatous overgrowth and less of 50% myometrial invasion [2][3][4][5][6][7][8][9][10][11][12]. Immunohistochemical markers commonly expressed by adenosarcoma are CD10 (71 to 100%) and WT1 (79%) while additional markers are smooth muscle actin (50 to 68%), CD34 (35%), desmin (32 to 62.5%), AE2/3 cytokeratin (25 to 27%) and vimentin (86%).…”
Section: Discussionmentioning
confidence: 99%
“…The high-risk factors might affect the prognosis of adenosarcoma [ 24 ] and therefore individualized treatment should be considered. In terms of adjuvant therapy, it has been shown that adenosarcoma recurrence with or without sarcoma overgrowth responds to the treatment regimen of ifosfamide or doxorubicin [ 25 ]. However, radiotherapy does not benefit the overall survival of patients, and there is insufficient evidence regarding the benefits of chemotherapy and hormone therapy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of adjuvant therapy, it has been shown that adenosarcoma recurrence with or without sarcoma overgrowth responds to the treatment regimen of ifosfamide or doxorubicin [ 25 ]. However, radiotherapy does not benefit the overall survival of patients, and there is insufficient evidence regarding the benefits of chemotherapy and hormone therapy [ 25 ]. Further studies are needed to determine the most effective adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%